Carbon currencies: A new gold standard for sustainable consumption? - Gill Seyfang (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2009)
Sustainable consumption demands radical changes to the socio-economic and socio-technical systems of provision in society, in order to realign development goals towards quality of life rather than material consumption. Complementary currencies (CCs - parallel media of exchange which run alongside mainstream money) have been proposed as new tools to achieve these goals. This paper reviews experience with CCs, along with an untested CC policy proposal known as Personal Carbon Trading (PCT), which proposes to issue carbon currency to all UK citizens, with the aim of limiting and reducing carbon emissions. However, the lack of empirical experience with PCT hinders its development. This paper makes the novel conceptual link between CCs and PCT, in order to inform its development. The following factors are significant in influencing their character, impacts and outcomes: policy coherence; social contexts and cultures; technologies; skills and capabilities; and finally, the extent to which the CCs enlist and engage with active citizenship. Hitherto neglected social and political factors are significant influences on the development and success or otherwise of CCs, and by definition, PCT. While much PCT literature approaches it as a utilitarian market system, this analysis suggests that PCT should instead be approached as a socially-embedded collective endeavour, as 'ecological citizenship' rather than 'ecological modernisation'.
Keywords: 330; carbon emissions; carbon allowances; environmental governance; climate change; degrowth; ecological citizenship; Klimaveränderung; Luftverunreinigung; Kohlendioxid; Gesellschaftliches Bewusstsein; Bürgerbeteiligung; Währung; Großbritannien